From experts practice of revealing obliterated and obscured notes and signatures - Bodrov, Nikolay (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article focuses on the analysis of practice, which allows for identification of hidden texts and signatures. The examples of subsequent handwriting researches of detected notes, signatures and people, on whose behalf they were made, are given. In this article there is a description of optical research of dashes, which were created by common and special pens. The author formulated all practical recommendations about working with research equipment, programs and creating illustrations phototable to expert testimony. There are several findings: 1 the aggressive impact on the document sometimes does not preclude the successful handwriting identification of the remote notes and signatures perpetrator; 2 based on the outcome of the practice analysis, it points to the need of joining two specialties: «technical and criminalistics examination» and «forensic handwriting examination» due to the fact that practicing experts in the handwriting field often make mistakes.
Keywords: kryminalistyka; kwestionowane dokumenty; kryminalistyczne badanie pisma ręcznego; podpisy